Предмет: Математика,
автор: AlenaLaim
Упростите выражение .
Приложения:
Ответы
Автор ответа:
0
1 можно представить как sin^2 (a/2)+cos^2(a/2);
a cos a= cos 2*(a/2); cos 2*(a/2)= cos^2 (a/2)-sin^2(a/2);
тогда данное выражение равно:
(sin^2(a/2)+cos^2(a/2)+cos^2(a/2)-sin^2(a/2))/cos(a/2)= 2cos^2(a/2)/cos(a/2)= 2 cos(a/2).
a cos a= cos 2*(a/2); cos 2*(a/2)= cos^2 (a/2)-sin^2(a/2);
тогда данное выражение равно:
(sin^2(a/2)+cos^2(a/2)+cos^2(a/2)-sin^2(a/2))/cos(a/2)= 2cos^2(a/2)/cos(a/2)= 2 cos(a/2).
Похожие вопросы
Предмет: Английский язык,
автор: milaya2007
Предмет: Английский язык,
автор: kirilovmaksim2
Предмет: Алгебра,
автор: oksssivanova
Предмет: Химия,
автор: Аноним
Предмет: Химия,
автор: kkavka2015